The Difference Between Movement and Self-Recognition in Children Performing the Standing Long Jump - Misako Yasue MS; Takeshi Ueda PhD; Tomohiro Fukuda MS; Tatsuya Adachi PhD; Yusuke Ozaki MS (SAGE Publishing, 2019)
This study examined the relationship between the recognition of movement and actual movement during the standing long jump. A total of 11 healthy elementary school children from 10 to 11 years of age participated in this study. Participants conducted standing long jumps (the target movement) after receiving video instruction. They were then tested on their recognition of the target movement according to an image. A total of 12 markers were then attached to each participant to measure the actual movements taken during subsequent performances of the target movement. They were then tested on the recognition of their own movements (a self-evaluation). The results were as follows: maximum shoulder angle was observed prior to each jump; this became successively lower in the image review, actual movement, and self-evaluation procedures. Knee flexion angle successively decreased in the actual, target, self-evaluation, and image movements during the railway crossing procedure. While jumping, the maximum shoulder angle was significantly larger in the target movement than the actual ( P < .01) movement, but the actual movement was significantly lower than the image ( P < .001) and self-evaluation ( P < .001) movements. The angle between the perpendicular from the acromion and the line segment connecting the acromion to the lateral malleolus successively decreased in the target, image, self-evaluation, and actual movements. Thus, there were obvious points at which it was either easier or more difficult for subjects to recognize movements. Points of relative ease and difficulty were also identified during performance of the target movement.